The influence of empirical and normative expectations on cooperation - Felix Kölle; Simone Quercia (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
In this paper, we investigate the joint influence of empirical and normative expectations on cooperative behavior. We conduct two experimental studies (n = 243) in which we separately elicit (i) behavior in a public goods game and (ii) social norms under the form of normative and empirical expectations. In a situation where individuals can decide conditionally on others' contributions, we find a strong norm of conditional cooperation whereby people find it socially appropriate to match others contribution and believe others to comply with such rule of behavior. In contrast, when there is strategic uncertainty regarding others' behavior, empirical and normative expectations diverge substantially. While individuals believe that contributing fully to the public good is the most appropriate action, they expect others to contribute only half of their resources. This renders normative expectations unpredictive for average behavior and underlines the importance of a close alignment of empirical and normative expectations for the influence of social norms on behavior.
Keywords: C92; D63; H41; 330; Cooperation; social norms; expectations; public goods; experiment